In Silico Peptide Repertoire of Human Olfactory Receptor Proteomes on High-Stringency Mass Spectrometry - Adhikari, Subash; Sharma, Samridhi; Ahn, Seong Beom; Baker, Mark S (Journal of proteome research, 2019)
Human olfactory receptors (ORs) are seven-pass transmembrane G-protein coupled receptors (GPCR) involved in smell perception and many other signaling pathways. They are primarily expressed in the olfactory epithelium and ectopically expressed in several other organs and tissues. neXtProt contains 4 PE1 (protein existence 1, evidenced at the protein level) ORs, determined on the basis of either protein interaction data (i.e., OR1D4 and OR2AG1) or convincing genetic, haplotype, or biochemical data (i.e., OR1D2 and OR2J3). Not a single OR currently qualifies for neXtProt PE1 status based on mass spectrometry (MS) evidence. Many reasons for this absence of MS-based identification have been proposed, including (i) confined or spatiotemporal or developmental expression, (ii) low copy number, (iii) OR repertoire gene silencing, and (iv) limited tissue availability. OR transmembrane domains (TMDs) inherently limit MS identification because the hydrophobic nature restricts the access of trypsin to potential cleavage sites. Equally, the extremely low frequency or lack of accessible arginine and lysine residues in TMDs renders trypsin cleavage ineffective. Here, we demonstrate an analytical approach specifically focused on the hydrophilic (trypsin-accessible) domains of ORs [i.e., with all transmembrane segments and anchored peptides excluded). We predicted the ability of OR soluble (hydrophilic) domains to yield 2 or more >9 amino acids (aa) length unique mapping (unique to a protein only), non-nested (peptides with varying length at the N or C terminal but containing the same core sequence), leucine/isoleucine (I/L) switch examined (I and L have same mass and cannot be distinguished by MS) tryptic peptides. Our analysis showed that ∼58% of the human OR proteome could potentially generate tryptic peptides that satisfy current the Human Proteome Project data interpretation guidelines (version 2.1) when no missed cleavages are allowed and increases to ∼78% when one missed cleavage is allowed. The utilization of current biological data (adjuvant genomics, expression profile, transcriptomics, epigenome silencing data, etc.) and the adoption of a non-conventional proteomics approach (e.g., Confetti multiprotease digestion, CNBr cleavage of TMDs, and more-extreme chromatographic and MS methods) could aid in the detection of the remaining ORs.